The ability of medium chain fatty acids (MCFA) to replace zinc oxide (ZnO) and common antimicrobials in nursery pig diets - Reynolds, Samantha N.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
There is increasing consumer pressure to limit the use of antimicrobials and ZnO in nursery pig diets. Studies have shown that medium chain fatty acids (MCFA) may be an effective alternative to replace ZnO and common antimicrobials. In this experiment, 360 weanling pigs (DNA 200 x 400; BW=5.4 0.07 kg) were used in a 35-d experiment to test the effects of ZnO, carbadox and MCFA on nursery pig growth performance. There were 6 pigs per pen (EU) and 10 pens per treatment. Pigs were assigned to pens in a completely randomized design. The dietary treatments were: 1) negative control; 2) carbadox (50g/ton) 3) 3,000 ppm ZnO in phase 1 and 1,500 ppm ZnO in phase 2; 4) 1% C6:C8:C10 (MCFA blend); 5) 1% Feed Energy R2 (Feed Energy Corp, Des Moines, IA); 6) 1% FORMI GML (ADDCON; Bitterfeld-Wolfen, Germany). Individual pig weights and feeder weights were taken weekly to calculate ADG, ADFI, and G:F. Treatments were fed in two phases (d 0 to 7 and d 7 to 19) while a common phase 3 diet was fed (d 20 to 35). Overall, body weights did not differ between treatments (P=0.06). During the treatment phases, pigs fed ZnO and carbadox had increased (P<0.05) ADG than those fed the R2 and control diet while FORMI and C6:C8:C10 diets had a comparable (P>0.05) ADG to pigs fed carbadox. Pigs fed ZnO had higher (P=0.0004) ADFI than those fed the control, C6:C8:C10 and R2 diets while pigs fed the FORMI GML had no significant difference (P<0.05) compared to those fed carbadox. Overall G:F did not differ (P=0.078) between the treatments. The results of this study suggest that overall, there is no significant difference (P>0.05) in growth performance between the 6 dietary treatments and therefore, further research on MCFA in nursery pig diets is recommended.
Keywords: Spring 2019